2006
DOI: 10.1021/jp064841p
|View full text |Cite
|
Sign up to set email alerts
|

DFT-Based Characterization of the Multiple Adsorption Modes of Nitrogen Oxides on Pt(111)

Abstract: Pt is the most common catalyst for NO oxidation to NO 2 , a key reaction in NO x remediation chemistry. In this work, density functional theory calculations and plane-wave supercell models are used to calculate the energies, charge distributions, and vibrational spectra of the stable and metastable states of adsorbed NO, NO 2 , and NO 3 on Pt(111), the most likely active metal face for this catalytic oxidation. NO, NO 2 , and NO 3 are all strong electron acceptors and bind to the Pt(111) surface via charge don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
80
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(101 citation statements)
references
References 77 publications
19
80
0
2
Order By: Relevance
“…Anyhow, our results suggest that NO undergoes oxidation on our sensors, which may be due to the presence of Pt in each sample (the electrode surfaces), in addition to the other metals/metal oxides decorating the WO 3 nanoparticles. 45,[50][51][52][53][54][55][56] 3.4.2. Hydrogen sulphide -H 2 S. Dwyer et al 57 have used XPS to investigate the interactions between tungsten oxide films and H 2 S gas at 475 K, close to our sensor operation temperature of 493 K. The WO 3 film was exposed to different concentrations of H 2 S gas and after each exposure, W 4f, O 1s and S 2p spectra were recorded.…”
Section: Gas Adsorption Behaviour On Metal and Metal-oxide Surfacesmentioning
confidence: 99%
“…Anyhow, our results suggest that NO undergoes oxidation on our sensors, which may be due to the presence of Pt in each sample (the electrode surfaces), in addition to the other metals/metal oxides decorating the WO 3 nanoparticles. 45,[50][51][52][53][54][55][56] 3.4.2. Hydrogen sulphide -H 2 S. Dwyer et al 57 have used XPS to investigate the interactions between tungsten oxide films and H 2 S gas at 475 K, close to our sensor operation temperature of 493 K. The WO 3 film was exposed to different concentrations of H 2 S gas and after each exposure, W 4f, O 1s and S 2p spectra were recorded.…”
Section: Gas Adsorption Behaviour On Metal and Metal-oxide Surfacesmentioning
confidence: 99%
“…Several review papers have summarized the development of the studies of the surface chemistry of NO on metal crystals [144][145][146][147][148]. Adsorption of NO on Pt surfaces is highly dependent on the surface structure and proceeds preferentially on steps sites, on which NO dissociation takes place, a process that is essential for NO reduction.…”
Section: Surface Chemistry Of No On Pt Surfacesmentioning
confidence: 99%
“…on well-defined metal surfaces has been researched extensively in recent years due to the fundamental interest and practical applications [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. In the case of Nb surfaces, the high-resolution electron energy loss spectroscopy (HREELS) has been used early to explore the adsorption of NO on the Nb(1 1 0) surface by Bartke et al [18] They found that parts of NO molecules adsorbed on the metal surface stably, while parts of NO molecules were dissociated.…”
Section: Introductionmentioning
confidence: 99%